ChatBot-based Bus Ticket Booking Prototype Using WhatsApp - Febriansyah , Bagas; Abdillah, Leon A. (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Customer relationship management (CRM) is the most critical part of any business's operations. To deploy CRM at PO Harapan Jaya, a ticket ordering system is required to make things easy for customers. Researchers constructed a chatbot prototype using the WhatsApp app with the goal of making it easier and more efficient for PO Harapan Jaya customers to buy bus tickets. The eXtreme Programming (XP) approach is a strategy for creating a ticket-booking chatbot prototype using WhatsApp. In developing the WhatsApp chatbot prototype for this research, a CRM system is proposed that can collect and manage information entered by customers, ticket purchase history, and produce proof of ticket reservations via WhatsApp chat, which will then be shown to the PO Harapan Jaya admin to obtain bus tickets ordered by customers. Researchers conducted a black box test on the prototype. This study intends to demonstrate how deploying chatbots in the WhatsApp application may speed up the bus ticket purchase process, increase customer service quality, and assist PO Harapan Jaya in optimizing CRM tactics. Based on the extensive programming processes, including planning, design, coding, and testing, it is possible to determine that the final WhatsApp chatbot will work properly and may be used by users to buy PO Harapan Jaya bus tickets. Customers may book tickets, examine departure schedules, and contact the PO Harapan Jaya admin if they have any issues when ordering tickets.